City, Climate, and Architecture A Theory of Collective Practice - Roesler, Sascha (Klima Polis, 2022)
The publication rethinks climate control through the lens of city climate phenomena. Based on a history of climate control on urban scales, it promotes the integration of indoors and outdoors in order to reduce environmental and thermal loads in cities.While the first part of the book focuses on the interwar period in Europe, the publication's second part considers examples from all over the globe until the late 20th century.